Ganti Kerugian Akibat Wanprestasi Perjanjian Kerja Sama (Bagi Hasil) Kajian KUHPERDATA - Alwi, Lala; Tjoanda, Merry; Radjawane, Pieter (KANJOLI Business Law Review, 2023)
The breach of contract in a cooperation agreement resulting in losses to the creditor as the capital provider constitutes a breach of contract. Thus, it is necessary to examine the legal relationship between the debtor and creditor, as well as the form of compensation for losses due to the breach of contract in the profit-sharing agreement. This research method is juridical-normative and is descriptive-analytical, utilizing an approach formulated within the results of literature research from primary, secondary, and tertiary legal materials analyzed and examined in a structured assessment. The research results indicate that the legal relationship between the debtor as the fund recipient and the creditor as the fund provider is governed by the cooperation agreement or profit-sharing, regulating the rights and obligations of both parties, including the legal relationship between the debtor and creditor referring to the relationship formed when the debtor takes a loan or receives credit from the capital provider (creditor). This relationship is governed by an agreement/contract that regulates the rights and obligations of both parties, covering various aspects such as the Agreement/Contract Relationship, financing, trust, and supervision relationships. In the event of a breach of promise by the debtor, the consequence in the form of compensation is the debtor's obligation to pay damages arising from the debtor's negligence as regulated in the Civil Code, consisting of three types: costs, losses, and interest. In connection with the above problem, even though the legal terms of lending have been agreed upon in the agreement/contract, the regulation of these legal relationships must also be included in the agreement to prevent future breaches that may cause losses to the capital provider (creditor).